Prediction of bitter pit in 'gala' apples by means of fruit infiltration with magnesium Predição de "bitter pit" em maçãs 'gala' por meio da infiltração dos frutos com magnésio - do Amarante C.V.T.* (2009)
Bitter pit is one of the main postharvest physiological disorders in apples. Fruit mineral analysis (concentrations of Ca, Mg, K, and N), normally used to assess bitter pit risk, is expensive and shows a low predictive potential. This has stimulated the development of alternative methods to predict at the preharvest period the postharvest risk of bitter pit occurrence. The objective of this work was to assess the feasibility of fruit infiltration with Magnesium (Mg) to predict the risk of bitter pit occurrence during cold storage of 'Gala' apples. In addition, Ca concentrations (mg kg-1 of fresh weight) in the flesh and skin tissues of the fruit with different levels of bitter pit severity and incidence, in both fruits, infiltrated with Mg or left in cold storage, were plotted to predict the risk of bitter pit in terms of Ca content. Fruits were harvested in an orchard with high incidence of bitter pit, in Lages, SC, in 2003/2004. Samples of fruits were harvested from 20 randomly marked trees, corresponding to 30 fruits for infiltration with Mg (harvested 20 days before the commercial maturity) and 100 fruits for cold storage (harvested at the commercial maturity). The levels of Ca in the fruits above those which there were low risk of bitter pit were similar among fruits infiltrated with Mg and those left in cold storage, corresponding to 55 and 192 mg kg-1 for flesh and skin tissues, respectively. The Ca concentration quantified in the skin tissue provided a better prediction of bitter pit risk than when quantified in the flesh tissue. The results showed that fruit infiltration with Mg represents a feasible method to assess the bitter pit risk during cold storage in 'Gala' apples grown in Southern Brazil.